Legal Urgency on Designing The Legislation for The Use of Artificial Intelligence in Indonesian Medical Practice - Hary Abdul Hakim; Chrisna Bagus Edhita Praja; Hardianto Djanggih (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
Artificial intelligence (AI) offers the potential for a great improvement in patient care, both in diagnose and disease treatment, and a consequential reduction in healthcare costs, a part of opportunities and challenge are ahead. The use of AI in medicine was significantly developed in some countries. Indonesia as a modern country also has a great change in promoting the use of AI. The study aims to propose on designing the legislation for the use of AI in Indonesian medical practices. The method used in this research is normative juridical approaches with descriptive analysis. The data used are primary legal material namely the Indonesian Penal Code and Law No. 36 of 2009 on Health Law. Meanwhile, the secondary legal material used are books, journals, and other legal documents. The results show that designing the new legislation as the guidance and basis for the use of AI shall give a good impact on the development of health services as practices among other countries. Moreover, Health Act 2009 clearly supported the use of advance technology’s product in medicine. Yet, the application of AI facilitates interpretation follows with high accuracy and speed for medical diagnoses.